Penentuan Awal Bulan Kamariah Untuk Ibadah - Fathor Rahman; Pujiono Pujiono; Siti Muslifah (LP2M UIN Sultan Aji Muhammad Idris Samarinda, 2020)
This paper presents data regarding the formula for determining the start of the month for worship at the time of the Prophet. This is important because the determination of the beginning of the month among Muslims has always been a polemic, even Muslims until now still do not have a definite and unique calendar to serve as a common guideline. The method usedin this research is the method introducedby Louay Safi